Using the wavelet transform to process data from experimental studies of the discontinuous plastic deformation effect (Fracture and Structural Integrity, 2024)
Vast number of theoretical and experimental works has been devoted to the study of discontinuous plastic deformation (the Portevin-Le Chatelier effect), which manifests itself for most widely used alloys in certain ranges of both temperatures and strain rates. Due to the statistical nature of this phenomenon, difficulties arise in processing, qualitative analysis and quantitative comparison of test results and calculations. Using of statistical methods for these purposes makes it possible to get only some averaged characteristics of the obtained data (usually - moments of the first and second orders in amplitudes and frequencies). A possible alternative for processing of experimental and theoretical results of this effect research is wavelet analysis using.The results of experimental studies of the Portevin–Le Chatelier effect, realized during the deformation of thin-walled tubular specimens made of aluminum alloy AMg6M at certain strain rates at room temperature are presented. Diagrams of deformation under uniaxial tension, shear, proportional and disproportionate loading of specimens were obtained. The inhomogeneity of strain fields and their rates is shown, illustrating the manifestation of the Portevin – Le Chatelier effect under conditions of complex loading of thin-walled tubular specimens made of AMg6M alloy. A brief overview of existing methods and means of non-destructive testing is presented that make it possible to non-contactly record the spatial heterogeneity of plastic yielding. Some possibilities of using the wavelet transform to process certain types of non-monotonic stress-strain diagrams obtained for the specimens made of the aluminum alloy in question are discussed. Using wavelet analysis, a compact presentation of data from field experiments in the form of amplitude-frequency characteristics was obtained. The scalograms analysis of specimen loading diagrams was carried out.
Keywords: Discontinuous plastic deformation; Portevin – Le Chatelier effect; experimental research results; Digital Image Correlation method; wavelet analysis